2021
DOI: 10.3389/fimmu.2021.672849
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin Synergizes With Mesenchymal Stromal Cells Attenuates Chronic Allograft Vasculopathy

Abstract: BackgroundChronic rejection characterized by chronic allograft vasculopathy (CAV) remains a major obstacle to long-term graft survival. Due to multiple complicated mechanisms involved, a novel therapy for CAV remains exploration. Although mesenchymal stromal cells (MSCs) have been ubiquitously applied to various refractory immune-related diseases, rare research makes a thorough inquiry in CAV. Meanwhile, melatonin (MT), a wide spectrum of immunomodulator, plays a non-negligible role in transplantation immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
(98 reference statements)
1
2
0
Order By: Relevance
“…Xue et al showed that DCs transduced with single immunoglobulin IL-1-related receptor (GIGIRR) exhibited immature properties, and thereby upregulating Treg populations in the spleens and lymph nodes, which in turn induces immune tolerance post-islet allografting [59]. Consistent with our previous studies [31,33,60], ERCs distinctly increased the percentage of splenic CD4 + CD25 + Foxp3 + Tregs in the present study. Furthermore, the overexpression of IL-37 can further induce a higher proportion of Tregs in the spleen and the graft.…”
Section: Discussionsupporting
confidence: 91%
“…Xue et al showed that DCs transduced with single immunoglobulin IL-1-related receptor (GIGIRR) exhibited immature properties, and thereby upregulating Treg populations in the spleens and lymph nodes, which in turn induces immune tolerance post-islet allografting [59]. Consistent with our previous studies [31,33,60], ERCs distinctly increased the percentage of splenic CD4 + CD25 + Foxp3 + Tregs in the present study. Furthermore, the overexpression of IL-37 can further induce a higher proportion of Tregs in the spleen and the graft.…”
Section: Discussionsupporting
confidence: 91%
“…As the favourite source of stem cell therapy, MSCs possess multipotency 23 . Several studies use MSCs to treat vascular IH 24–26 . However, the role of MSCs in vascular injury remains to be fully elucidated, and the treatment effect of MSCs alone is not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Several studies use MSCs to treat vascular IH. 24 , 25 , 26 However, the role of MSCs in vascular injury remains to be fully elucidated, and the treatment effect of MSCs alone is not satisfactory. Therefore, in this work, lncRNA was used to improve the function of MSCs to enhance the therapeutic effect of MSCs.…”
Section: Discussionmentioning
confidence: 99%